The effect of laparotomy on hydroxyl radicals, singlet oxygen and antioxidants measured by EPR method in the tails of rats - Fricova, Jitka; Stopka, Pavel; Krizova, Jana; Yamamotova, Anna; Rokyta, Richard (Neuro endocrinology letters, 2009)
OBJECTIVES: The aim of the study was to demonstrate that direct measurement of hydroxyl radicals and singlet oxygen in the tail of living rats is possible. The basic level of hydroxyl radicals and singlet oxygen were measured and the effects of antioxidants on their levels were studied in the tail of living anaesthetized rats after acute postoperative pain. Laparotomy was performed as the source of acute abdominal pain. After closure of the abdominal cavity, the animals began to awaken within 30-60 minutes. They were left to recover for 2-3 hours; then they were reanesthetized and the effect of antioxidants was measured on the numbers of hydroxyl radicals and singlet oxygen via blood in the tail. METHODS: The laparotomy was preformed under general anesthesia (Xylazin and Ketamin) using Wistar rats. After recovery and several hours of consciousness they were reanaesthetized and free radicals and singlet oxygen were measured. An antioxidant mixture (vitamins A, C, D and Selenium) was administered intramuscularly prior to the laparotomy. All measurements were done on the tail of anaesthetized animals. In this particular article, the effect of antioxidants is only reported for hydroxyl radicals. RESULTS: After laparotomy, which represented both somatic and visceral pain, hydroxyl radicals and singlet oxygen were increased. Antioxidant application prior to laparotomy decreased the numbers of hydroxyl radicals. CONCLUSION: Results are in agreement with our previous finding regarding the increase in hydroxyl free radicals and singlet oxygen following nociceptive stimulation, in this case a combination of both somatic and visceral pain. The administered antioxidants mitigated the increase. This is further confirmation that direct measurement of free radicals and singlet oxygen represents a very useful method for the biochemical evaluation of pain and nociception.
Keywords: Animals; Laparotomy; Antioxidants; Rats, Wistar; oxidační stres; Tail; laparotomie; Oxidative Stress; hydroxylový radikál; Singlet Oxygen; Electron Spin Resonance Spectroscopy; bolest; Male; antioxidancia; ocas; krysa rodu Rattus; Pain; elektronová paramagnetická rezonance; zvířata; mužské pohlaví; singletový kyslík; Rats; Hydroxyl Radical; potkani Wistar